To the question of the content of educational programs in the muslim schools of Kazakhstan - Razdykova, G.M.; Salimov, F.N. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article various sources and literature including post-revolutionary literature of the second half of the 20th century and the beginning of the 21st century are presented. New ethnographic materials will give a broader perspective on the content of academic programs in Muslim schools. Teaching and methodological literature in Muslim maktabs (mostly refers to elementary schools where children are taught reading, writing, grammar and Islamic studies) was represented both by handwritten and printed textbooks and teaching aids. Such textbooks and teaching aids meant specially written books for certain disciplines. Handwritten books were widely used in the Muslim maktabs. Over the years many of the manuscripts had been published in numerous later editions. Learning and teaching support was mainly focused on compilation of school curriculum. The first school curriculum for «new-method» schools was compiled by I. Gasprinsky in 1898. It was called «Rahbar Mogallimin» and consisted of a subject schedule, basics of teaching by the sound method, lesson plans, as well as examples of lessons schedule with the amount of academic hours. Textbooks for maktabs, which were widespread in the Governor-Generalship of the Steppes, were mostly published not in Kazakh, but in Tatar. They outlined the main provisions of the Islamic religion. The educational and methodological basis of the pedagogical system of Kazakhstan preserved the obsolete features.
Қазақстандағы мұсылман мектептерінде білім беру бағдарламаларының мазмұны туралы
К вопросу о содержании образовательных программ в мусульманских школах Казахстана
Keywords: Muslim schools; Kazakh literature; Islam; culture; religious and spiritual literature; school curriculum; ethnography of Kazakhs